Needs assessment survey regarding effectiveness of chronic care in Diabetes in a hospital setting - Yamna Jadoon; Abiha Abdullah; Qureshi, Asra; Jaleed Ahmed Gilani; Khan, Unab (Journal of the Pakistan Medical Association, 2022)
Objectives: To assess the current knowledge level about diabetes and acceptance of nurse-led educational programmes among diabetic patients. Method: The cross-sectional study was conducted at a community health centre in Karachi from August, 2018 to December, 2019 and comprised adult patients of ether gender with diabetes. Data was collected using a predesigned questionnaire to record demographic information, participants’ DM knowledge, self-management aspects and their opinions along with preferences for a DM educational support group. Data was analysed using STATA/SE 15.1. Results: Of the 215 participants, 80(37%) were males and 135(63%) were females. The overall mean age was 55.814.5 yrs. Most participants had diabetes for 5 years 127(59%) and 141(66%) did not know their type of diabetes. Most participants were prescribed anti-diabetic medications 201(94%), and 45(2%) had forgotten to take their medication recently. Insulin was being used by 65(30%) participants, and, among them, 27(42%) reused syringes. Most patients struggled to make lifestyle modifications 133(62%), and 144 (67%) were willing to attend nurse-led diabetic education sessions. Conclusion: There was found to be a need of diabetes education support programme to address knowledge deficiencies, and a nurse-led programme was found to be acceptable to the majority of study subjects. Key Words: Diabetes mellitus, Diabetes complications, Tertiary prevention, Health educators.